2013
DOI: 10.1155/2013/329549
|View full text |Cite
|
Sign up to set email alerts
|

Axial-Compressive Behavior, Including Kink-Band Formation and Propagation, of Singlep-Phenylene Terephthalamide (PPTA) Fibers

Abstract: The mechanical response ofp-phenylene terephthalamide (PPTA) single fibers when subjected to uniaxial compression is investigated computationally using coarse-grained molecular statics/dynamics methods. In order to construct the coarse-grained PPTA model (specifically, in order to define the nature of the coarse-grained particles/beads and to parameterize various components of the bead/bead force-field functions), the results of an all-atom molecular-level computational investigation are used. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Grujicic et al 56,[62][63][64][65] reported that defect's type, size and concentration are sensitive functions of the PPTA fiber fabrication (polymer synthesis, dope preparation and spinning process) -which are summarized in the present review in section 2.…”
Section: Structural Defectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Grujicic et al 56,[62][63][64][65] reported that defect's type, size and concentration are sensitive functions of the PPTA fiber fabrication (polymer synthesis, dope preparation and spinning process) -which are summarized in the present review in section 2.…”
Section: Structural Defectsmentioning
confidence: 95%
“…An outstanding analysis of PPTA fibers at multi scale levels is investigated by Grujicic et al 56,[62][63][64][65] . The computational investigations properly described the material models which are used to achieve the material (PPTA) behaviour at the length-scale levels from chemical structure (atoms) to composite structure (laminate) with brief description in eight levels.…”
Section: Ppta Computational Modellingmentioning
confidence: 99%
“…For example, studies have been performed to predict the ideal molecular geometry and chain conformations [13,74], elastic moduli [38,72], and compressive failure due to chain buckling [37]. The more recent work of Grujicic et al [20,21,22,24,23,25] represents the most comprehensive set of studies to date. These studies focused on modeling various defect patterns and impurities, as well as tensile, torsion, and compressional loading, and the resulting elastic moduli and axial strength of PPTA crystals.…”
mentioning
confidence: 99%
“…Examination of the results reported in Tables 2 -fibril axial-strength probability density function; and (b) the corresponding cumulative distribution function determined in the present work using molecular-type computational analyses. and σ 1 are found to be nearly equal to their fibril counterparts; (ii) the fiber transverse normal stiffness, E 22 =E 33 , is found to be nearly equal to the more compliant E 33 fibril modulus; and (iii) All three shear moduli G 12 , G 13 and G 23 are found to be nearly equal to the same value, the value which is controlled by the compliant PPTA inter-sheet sliding resistance (i.e. G 12 of the fibrils); and (e) To assess the yarn-level stiffness and strength properties from the known fiber properties, additional effects arising from the fiber-twist-induced inter-fiber friction had to be taken into account.…”
Section: Fibrils Fibers and Yarns Figures 1(e)-(g)mentioning
confidence: 93%
“…The resulting defects can also degrade mechanical properties of the PPTAbased materials, and their effect has to be accounted for in the analysis of the ballisticprotection resistance of the PPTA-based materials. To address this problem, a series of allatom and coarse-grained molecular-level computational analyses is carried out in the present work [11][12][13]. Specifically, the effect of the preludial handling-induced deformation modes such as fiber/yarn transverse compression due to inter-yarn contacts, fiber/yarn twist/axialcompression, and fiber/yarn bending (encountered primarily in warp yarns) and the associated formation of kink-bands has been investigated.…”
Section: Effect Of Fiber-/yarn-handling-induced Defects On Ppta-fibermentioning
confidence: 99%